Successful Surgical Retrieval of Thoracic Esophageal Foreign Body in A Holstein Friesian Cross Cow - M. Madeena Begum; V. Vijayanand; A. Sabarinathan; M. Nandhini; M. Balagangatharathilagar (The Indian Veterinary Journal, 2023)
An eight year old Holstein Friesian cross breed cow was presented with a history of abdominal distension and animal has not voided for past 3 days. On clinical examination, conjunctival mucous membrane was congested and the animal was dehydrated. Physical examination of the animal revealed, swelling at the submandibular region and tympany of left paralumbar fossa. Radiological examination of the animal revealed, presence of foreign body in esophagus at the level of thoracic inlet. Hence, the case was diagnosed as esophageal obstruction (Choke).  Under general anaesthesia, esophagotomy was performed and the esophageal foreign body (Nylon rope) was retrieved. Post operative antibiotic and supportive therapy was administered for 5 days. Suture removal was done on 7th post operative day. The animal made an uneventful recovery.